AGRONOMIC BIOFORTIFICATION OF BEET PLANTS WITH ZINC VIA SEED PRIMING - Vergara Carmona, Victor Manuel; Cecilio Filho, Arthur Bernardes [UNESP]; De Almeida, Hilario Junior; Silva, Gilda Carrasco; Dos Reis, Andre Rodrigues [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2020)
One-fifth of the world's population consumes too little zinc (Zn) causing deficiencies that can damage cells, stunt growth, and decrease immune response. This study evaluated the effect of time on the priming of beet seeds, in solutions enriched with Zn, on physiology, growth, production, and root biofortification. Two greenhouse experiments were conducted during spring 2015 and autumn 2016. In each experiment, 24 treatments were tested which comprised various combinations of three Zn concentrations (0, 10, and 30 mg mL(-1)), two Zn sources (sulphate and chloride), and four time periods (12, 16, 20, and 24 h), arranged in a randomised block design with four replicates. The concentration of Zn, mainly as sulphate, affected all parameters evaluated in the beet plants, such as fresh and dry root mass, photosynthesis, and root Zn concentration (biofortification). Compared to the control, fresh root mass increased 70 and 100 g per plant with 10 mg mL(-1) of Zn during the experiments in 2015 and 2016, respectively. The same concentration for 16 h produced the highest Zn concentration in the roots, achieving 121 and 42 mg kg(-1) in 2015 and 2016, respectively. Priming seeds in solutions enriched with Zn, thus, benefited the physiological response of the beet plants by promoting increases in growth, production, and biofortification of beet roots. Therefore, this method can be used to biofortify beet plants agronomically, regardless of the Zn source.
Keywords: Beta vulgaris var; vulgaris; Nutritional value; Seed treatment; Micronutrient